ANALISIS BERPIKIR KRITIS MATEMATIS BERDASARKAN PEMBELAJARAN STUDENT FACILITATOR AND EXPLAINING KEMANDIRIAN BELAJAR PESERTA DIDIK - Ahmad Abdul Azis; Yuberti Yuberti; Indah Resti Ayuni Suri (Journal of Mathematics Education and Science, 2020)
The purpose of this research is to analyze student facilitators and explaining models on critical thinking mathematically. Analyzing the level of self-reliance learning on critical math learners' ability, analyzing student facilitators' interaction, and explaining critical thinking critical math and self-reliance learners. Research conducted in class X SMK Muhamadiyah 2 Bandar Lampung. This type of research is Quasi-Experimental Design. Sampling techniques are done in a simple Random Sampling; data collection techniques are conducted through tests and nontest. The type of test to think critically about mathematical mathematics is an objective test that is a matter of description (essay), testing this hypothesis using variance analysis (ANAVA) Two paths with unequal cells. The results of learning data analysis of Student Facilitator and Explaining the ability of critical thinking mathematically better than conventional learning models. The high learning of students, the better the ability to think critically of students mathematically. There is no interaction between Student Facilitator and Explaining learning models and the self-reliance learning level towards learners' mathematical thinking skills. Tujuan penelitian ini ialah menganalisis model Student Facilitator and Explaining terhadap berpikir kritis matematis, menganalisis kemampuan berpikir kritis matematis kemandirian belajarerhadap peserta didik, menganalisis interaksi Student Facilitator and Explaining terhadap berpikir kritis matematis dan kemandirian peserta didik.Penelitian dilakukan di kelas X SMK Muhamadiyah 2 Bandar Lampung.Jenis penelitian Quasi Experimental Design.Pengambilan sampel dilakukan secara Simpel Random Sampling. Teknik pengumpulan data dilakukan melalui tes dan non tes. Jenis tes untuk Berpikir Kritis Matematis matematika adalah tes obyektif yaitu berupa soal (essay). Pengujian hipotesis ini dengan analisis variansi (ANAVA) dua jalan dengan sel tak sama. Adapun hasil analisis data pembelajaran Student Facilitator and Explaining terhadap kemampuan berpikir kritis lebih baik dari model pembelajaran konvensional. tingginya kemandrian belajar peserta didik maka semakin baik kemampuan berpikir kritis peserta didik. Tidak terdapat interaksi antara model pembelajaran Student Facilitator and Explaining dan tingkat kemandirian belajar terhadap kemampuan berpikir kritis peserta didik.